1994
DOI: 10.1080/09540129408258670
|View full text |Cite
|
Sign up to set email alerts
|

Controlled evaluation of a brief intervention of HIV prevention among injecting drug users not in treatment

Abstract: This study evaluated the effectiveness of a brief intervention (BI), a one-session motivational interview, in reducing HIV risk-taking behaviour among injecting drug users (IDU) not enrolled in any form of treatment for drug dependence. IDU were randomly assigned to either BI or a non-intervention control condition (NIC). One hundred and twenty-one subjects were successfully contacted for a 3-month follow-up and 88 subjects were followed up at 6 months. There were significant reductions for the sample as a who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 22 publications
(16 reference statements)
2
25
0
Order By: Relevance
“…34 HIV/STI prevention within jail systems could test brief, even single-session, risk reduction interventions, which have been shown effective in various populations. [50][51][52] Additionally, HIV prevention studies could recruit participants from jail settings and implement prevention interventions upon community reentry-a highrisk window of opportunity for intervention. 53,54 Providing HIV/STI prevention services to non-incarcerated arrestees could be accomplished in community settings such as probation and alternative to incarceration programs.…”
Section: Discussionmentioning
confidence: 99%
“…34 HIV/STI prevention within jail systems could test brief, even single-session, risk reduction interventions, which have been shown effective in various populations. [50][51][52] Additionally, HIV prevention studies could recruit participants from jail settings and implement prevention interventions upon community reentry-a highrisk window of opportunity for intervention. 53,54 Providing HIV/STI prevention services to non-incarcerated arrestees could be accomplished in community settings such as probation and alternative to incarceration programs.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational Interviewing has been used effectively to improve a range of health behaviors, including safer sex practices, albeit among HIV-negative persons (Belcher et al, 1998;Picciano, Roffman, Kalichman, Rutledge, & Berghuis, 2001;Reitman et al, 1996). Three of five studies that tested MI interventions addressing risky sexual practices of HIV negative people (Baker, Healther, Wodak, Dixon, & Holt, 1993;Baker, Kochan, Dixon, Heather, & Wodak, 1994;Belcher et al, 1998;Picciano et al, 2001;Reitman et al, 1996) found significantly improved condom use and/or a decrease in unprotected sexual intercourse compared with controls. Brief, MI-style interventions have been used successfully among patients with HIV, but primarily to improve antiretroviral treatment (ART) adherence (Adamian et al, 2004;Diorio et al, 2003;Golin et al, 2006;Safren et al, 2001).…”
Section: Rationale For a Motivational Interviewing-based Interventionmentioning
confidence: 95%
“…In response, there is a growing literature on the use of motivational enhancement therapy for both brief and extended individual HIV risk reduction counseling, including therapy for HIV+ persons and individuals with co-morbidity with alcohol or drug problems (see, e.g., Baker, Kochan, Dixon, Heather, & Wodak, 1994;Beadnell et al, 1999;Koblin, Chesney, Coates, & EXPLORE Study Team, 2004;Ryan, Fisher, Peppert, & Lampinen, 1999). Such counseling interventions have been developed partly in response to evidence that motivational enhancement therapy is effective for a broad range of problem health behaviors, including obesity, medication schedule noncompliance for diabetes, and substance abuse (for reviews, see Dunn, Deroo, & Rivera, 2001;Nahom, 2005).…”
Section: Introductionmentioning
confidence: 97%